Personalizmas ir ekologija: Roberto Spaemanno antropomorfizmo reabilitavimas. - Jokubaitis, Linas (Problems / Problemos, 2025)
The paper presents the argument that Spaemann's ecological thought is grounded in his attempt to find an alternative to the problems which he sees as originating in the rejection of teleological understanding of human beings and nature. The paper argues that Spaemann's ethical personalism and reflections on ecological problems are not two separate fragments of his philosophy, which have no clearer relation. A personalist perspective is inseparable from Spaemann's efforts to rehabilitate anthropomorphisms, which he sees as a necessary condition for the establishment of ethical relationship with nature. The paper defends the thesis that philosopher's attempt to rehabilitate anthropomorphisms is the link which connects his ecological and personalist ethics. The personalist perspective marks an attempt to find an alternative to the ever-intensifying domination of modern anthropocentrism, which is characterised by an inability to grasp the reality of person and nature.